2006
DOI: 10.1021/jp063211k
|View full text |Cite
|
Sign up to set email alerts
|

Infrared Spectroscopy of Competitive Interactions between Liquid Crystals, Metal Salts, and Dimethyl Methylphosphonate at Surfaces

Abstract: We report the use of Fourier transform polarization modulation infrared reflection-absorption spectroscopy (PM-IRRAS) to characterize the influence of dimethyl methylphosphonate (DMMP) on the molecular interactions occurring within thin films of nitrile-containing liquid crystals supported on surfaces presenting metal perchlorate salts. Infrared spectra obtained using thin films of 4'-octyl-4-biphenylcarbonitrile (8CB) supported on copper(II) perchlorate salts reveal the nitrile groups of 8CB to be coordinated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
93
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 46 publications
(102 citation statements)
references
References 41 publications
9
93
0
Order By: Relevance
“…Overall, these results along with similar results reported in the literature [31,38] provide strong support for the proposition that metal salts can be used to prepare a class of chemically functionalized surfaces at which LCs can be oriented through metal ion-LC coordination interactions involving the nitrile group of the LC. As discussed below, these coordination interactions can be disrupted by targeted chemical analytes, thus leading to a class of LC-based sensors for coordinating compounds.…”
Section: Surfaces Decorated With Metal Saltssupporting
confidence: 87%
See 2 more Smart Citations
“…Overall, these results along with similar results reported in the literature [31,38] provide strong support for the proposition that metal salts can be used to prepare a class of chemically functionalized surfaces at which LCs can be oriented through metal ion-LC coordination interactions involving the nitrile group of the LC. As discussed below, these coordination interactions can be disrupted by targeted chemical analytes, thus leading to a class of LC-based sensors for coordinating compounds.…”
Section: Surfaces Decorated With Metal Saltssupporting
confidence: 87%
“…Several key characteristics of the DMMP-induced ordering transitions are described in Figures 15.7E and F. Firstly, Figure 15.7E demonstrates that the DMMP-induced ordering transitions are reversible [25,31,33,36,39]. Secondly, Figure 15.7F reveals that the LC responds to concentrations of DMMP that are in the 10s of parts-per-billion range [25].…”
Section: Lc-based Sensors For Coordinating Compoundsmentioning
confidence: 96%
See 1 more Smart Citation
“…Inspired by that, bio/chemically modified substrates have been explored to control LC ordering and designed for detecting biomolecules [9][10][11][12][13][14] or chemicals [15][16][17][18][19][20]. For example, as shown in Figure 3(a), the gold substrate was first treated with a mixture of biotin-(CH 2 ) 2 [(CH 2 ) 2 O] 2 NHCO(CH 2 ) 11 SH (BiSH) and CH 3 (CH 2 ) 7 SH (C 8 SH).…”
Section: Lc-solid Interfacesmentioning
confidence: 99%
“…Apart from decorating the solid substrates with ligands for detecting proteins, it is also feasible to modify the surface with chemical receptors for chemical detection [15][16][17][18][19][20]. Figure 4 showed that depending on the surface topology and chemical composition, 5CB aligned on the plane with orientation depicted in Figure 4(c).…”
Section: Lc-solid Interfacesmentioning
confidence: 99%